Inffect of Composition Growing Medium on the Production and Quality for White Oyster Mushrooms (Pleurotus ostreatus - Fitriani, Yolanda Prastika; Nursandi, Fatimah; Wahono (Universitas Muhammadiyah Malang, 2022)
Oyster mushroom (Pleurotus ostreatus) has a high nutritional content and is low in fat. Oyster mushrooms have the advantage that they can grow in various media (on woody tree trunks) and other media such as sawdust, corn straw, bagasse, peanut shells, and other similar media. Mushrooms are foodstuffs that have a high nutritional content. One type of mushroom that is often consumed is oyster mushrooms. Oyster mushrooms are high in carbohydrates and protein but low in fat. The need for oyster mushrooms every year has increased by 5%, so that in 2015 the need for oyster mushrooms reached 21.9 tons / year. Growing media is one of the important factors that greatly affect the growth of fungi. The substrate of the fungus must be high in organic matter. Some alternative materials that can be used as material for mushroom media come from agricultural waste or waste such as corn straw and bagasse. The purpose of this study is to obtain a combination of media compositions in the cultivation of white oyster mushrooms that are appropriate for the production and quality of white oyster mushrooms. This research was carried out at the Agrotechnology Education Park (TAMESIA), Faculty of Agriculture and Animal Husbandry, University of Muhammadiyah Malang in December 2021 – June 2022. The resources obtained were analyzed using a simple Non-Factorial Completely Randomized Design / (RAL) which was then further tested using BNJ level of 5%. The treatment response showed an influence on the growth of the mycelium, the wet weight of the harvest, harvest dry weight as well as the nutrient content of white oyster mushrooms.